APPLICABILITY OF THE WELL OPERATED CONDITIONS FOR THE SOLUTION OF MIXED PROBLEM ATTRIBUTED TO SCHR?DINGER EQUATION (Journal of Sciences, Islamic Republic of Iran)
As a sequel of the recent works, we would like to discuss another stage for the solution of the mixed problem which considers the concepts of well operated conditions applicable to the solution of mixed problem, i.e. the existence and uniqueness of the solution must always conformable with some assumptions.